Ageing and interferon gamma response drive the phenotype of neutrophils in the inflamed joint - Grieshaber-Bouyer, Ricardo; Exner, Tarik; Hackert, Nicolaj S.; Radtke, Felix A.; Jelinsky, Scott A.; Halyabar, Olha; Wactor, Alexandra; Karimizadeh, Elham; Brennan, Joseph; Schettini, Jorge; Jonsson, Helena; Rao, Deepak A.; et al. (Annals of the Rheumatic Diseases, 2022)
Objective Neutrophils are typically the most abundant leucocyte in arthritic synovial fluid. We sought to understand changes that occur in neutrophils as they migrate from blood to joint. Methods We performed RNA sequencing of neutrophils from healthy human blood, arthritic blood and arthritic synovial fluid, comparing transcriptional signatures with those from murine K/BxN serum transfer arthritis. We employed mass cytometry to quantify protein expression and sought to reproduce the synovial fluid phenotype ex vivo in cultured healthy blood neutrophils. Results Blood neutrophils from healthy donors and patients with active arthritis showed largely similar transcriptional signatures. By contrast, synovial fluid neutrophils exhibited more than 1600 differentially expressed genes. Gene signatures identified a prominent response to interferon gamma (IFN-γ), as well as to tumour necrosis factor, interleukin-6 and hypoxia, in both humans and mice. Mass cytometry confirmed that healthy and arthritic donor blood neutrophils are largely indistinguishable but revealed a range of neutrophil phenotypes in synovial fluid defined by downregulation of CXCR1 and upregulation of FcγRI, HLA-DR, PD-L1, ICAM-1 and CXCR4. Reproduction of key elements of this signature in cultured blood neutrophils required both IFN-γ and prolonged culture. Conclusions Circulating neutrophils from patients with arthritis resemble those from healthy controls, but joint fluid cells exhibit a network of changes, conserved across species, that implicate IFN-γ response and ageing as complementary drivers of the synovial fluid neutrophil phenotype.
CRIS-Team Scopus Importer:2023-10-02